Risk Assessment of Effects of Essential Oils on Honey Bees (Apis mellifera L.) - Joel Caren; Yu-Cheng Zhu; Quentin D. Read; Yuzhe Du (Insects)
The toxicity of synthetic pesticides to non-target organisms has prompted a shift towards more environmentally friendly agricultural pest control methods, including the use of essential oils as possible biopesticides. Before these natural chemicals can be widely adopted for protecting food supplies and human health, it is crucial to evaluate their impacts on pollinators, such as honey bees. In this study, we examined the effects of one commercially available essential oil mixture (EcoTec+) and four essential oil components (β-bisabolene, cinnamaldehyde, 1,8-cineole, and eugenol) on honey bee workers using feeding or spray treatment. We then assessed the responses of esterase (EST), glutathione-S-transferase (GST), acetylcholine esterase (AChE), and P450. EcoTec+ increased the P450 transcript, while bisabolene inhibited EST and AChE, increased GST, and caused a mixed P450 response without being lethal. Cinnamaldehyde exhibited toxicity when ingested, suppressing P450 and eliciting a mixed response in AChE. Cineole inhibited EST but caused a mixed P450 response. Eugenol suppressed EST and AChE and was toxic on contact. We also assayed combinations of each compound with four synthetic formulations representative of the major pesticide categories, though no significant interactions were found. Overall, the essential oils tested did not cause acute lethal toxicity to honey bees; however, their biochemical effects varied, mostly remaining sublethal. These findings suggest that these essential oils could be considered safe for use around honey bees.